Rancang Bangun Aplikasi Materi Alat Ukur Jaringan Dan Telekomunikasi Dengan Metode Rapid Application Development - Apriyaldi, Muhamad Mumu; Rahmawati, Diah; Djamaludin, Djamaludin (JURNAL ILMIAH FAKULTAS TEKNIK, 2025)
The learning of network and telecommunication measuring instruments at SMK Nurul Hikmah is hindered by limited practical equipment and conventional teaching methods, making it difficult for students to understand concepts and reducing their learning interest. This study developed an application based on Augmented Reality and interactive quizzes to provide a more visual and engaging learning experience. The application utilizes Unity 3D, Maxst SDK, and Blender for creating 3D objects. The development method used is Rapid Application Development (RAD) to ensure a faster process and meet user needs. Key features include displaying 3D measuring instruments along with descriptions of their functions and operations, as well as interactive quizzes. Evaluation using the System Usability Scale (SUS) yielded an average score of 81.67%, indicating that the application is feasible and effective as a learning medium. This research is expected to encourage the adoption of interactive technology in education.